Pengaruh Neraca Pembayaran, Penanaman Modal Dalam Negeri Dan Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia - Sri Kinanti; Hilmiatus Sahla (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the effect of Balance of Payments, Domestic Investment, and Inflation on Economic Growth in Indonesia. The data used are secondary data in the form of quarterly data from 2017–2024. The results showed that partially, the Balance of Payments does not have a significant effect on Economic Growth with a tcount value of 0.709554 < ttable 2.04523 and a probability value of 0.4838 > 0.05. Domestic Investment also does not have a significant effect on Economic Growth with a tcount value of 1.873830 < ttable 2.04523 and a probability value of 0.0714 > 0.05. Meanwhile, Inflation has a positive and significant effect on Economic Growth with a tcount value of 2.668975 > ttable 2.04523 and a probability value of 0.0125 < 0.05. Simultaneously, the Balance of Payments, Domestic Investment, and Inflation have significant effect on Economic Growth with Fcount value of 3.421897 > Ftable 2.960 and a probability value of 0.030711 < 0.05. The Adjusted R Square value is 0.189875, which means that 18.98% of the variation in Economic Growth can be explained by the Balance of Payments, Domestic Investment, and Inflation, while the remaining 81.02% is influenced by other variables outside the research model.